2005
DOI: 10.1002/ana.20365
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism and serotonin receptors in the frontotemporal lobe degeneration

Abstract: In patients with the frontal variant of frontotemporal lobar degeneration (fv-FTLD), behavioral abnormalities may vary from apathy with motor slowness (apathetic form) to disinhibition with agitation (disinhibited form). These clinical presentations may be related to specific regional cerebral dysfunction and to deficit in the serotoninergic system. We studied cerebral glucose uptake using (18)F-fluorodeoxyglucose and positron emission tomography in 18 patients fulfilling clinical criteria for fv-FTLD and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 47 publications
(135 reference statements)
9
99
1
5
Order By: Relevance
“…Functional brain imaging study was consistent with dorsolateral and frontal medial hypoperfusion, in accordance with previous work on apathetic presentation of bvFTD [Franceschi et al, 2005].…”
Section: Discussionsupporting
confidence: 90%
“…Functional brain imaging study was consistent with dorsolateral and frontal medial hypoperfusion, in accordance with previous work on apathetic presentation of bvFTD [Franceschi et al, 2005].…”
Section: Discussionsupporting
confidence: 90%
“…Previous cross-sectional neuroimaging studies have consistently shown that FTD is associated with atrophy or decreased metabolism in this region compared to controls or other dementias (Ishii et al, 1998;Garraux et al, 1999;Rosen et al, 2002;Varrone et al, 2002;Salmon et al, 2003;Boccardi et al, 2005;Franceschi et al, 2005;Jeong et al, 2005;Williams et al, 2005). The other regions that showed longitudinal loss of gray matter (the medial temporal, medial frontal, and insular cortices) are heavily anatomically interconnected with the anterior cingulate and with each other.…”
Section: Discussionmentioning
confidence: 93%
“…However, this finding remains controversial, because assessment of the magnitude of hippocampal hypometabolism on 18 F-FDG PET is less reliable and as such is less recognized on visual inspection. Furthermore, hippocampal and medial temporal glucose hypometabolism can be prominent in some subtypes of FTD (68,69). Cerebral glucose metabolic activity is an index of synaptic function and density (19,20), but hypometabolism is not specific for AD and is observed in other neurodegenerative disorders.…”
Section: Pathophysiology Of 18 F-fdg Metabolism and Investigational Smentioning
confidence: 99%